Lymphocyte to monocyte ratio predicts survival and is epigenetically linked to miR-222-3p and miR-26b-5p in diffuse large B cell lymphoma - Ayman Mohamed Metwally; Ameera Abdel Hamed Mahmoud Kasem; Magda Ismail Youssif; Safia Mohammed Hassan; Abdel Hady A. Abdel Wahab; Lobna Ahmed Refaat (Scientific Reports, 2023)
Abstract Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma. 10–20% of the patients present with bone marrow (BM) involvement which predicts a worse survival. This study aimed to determine the prognostic significance of serum miR-222-3p, miR-26b-5p, EBV-miR-BHRF1-2-5p, and EBV-miR-BHRF1-2-3p and correlate their levels to clinical and haematological markers in DLBCL with special emphasis on the lymphocyte-monocyte ratio (LMR) and neutrophil-monocyte ratio. We also studied the role of BM BMI1 and PIM2 proteins in predicting BM infiltration. Serum miRNAs were studied on 40 DLBCL and 18 normal individuals using qRT-PCR. BMI1 and PIM2 proteins were studied on BM biopsies by immunohistochemistry. The results were correlated with clinical and follow-up data. All the studied miRNAs were dysregulated in DLBCL serum samples. BMI1 and PIM2 were expressed in 67% and 77.5% of BM samples, respectively. LMR was significantly associated with disease-free survival (DFS) (P = 0.022), miR-222-3P (P = 0.043), and miR-26b-5p (P = 0.043). EBV-miR-BHRF1-2-3p was significantly correlated to haemoglobin level (P = 0.027). MiR-222-3p, miR-26b-5p, and EBV-miR-BHRF1-2-5p expressions were significantly correlated to each other (P = 0.001). There was no significant correlation between the studied markers and follow-up data. LMR is a simple method for predicting survival in DLBCL. MiR-222-3p and miR-26b-5p may be implicated in an immunological mechanism affecting patients’ immunity and accordingly influence LMR. The correlation between miR-222-3p, miR-26b-5p, and EBV-miR-BHRF1-2-5p may indicate a common mechanism among the 3 miRNAs that may explain DLBCL pathogenesis.